2020
DOI: 10.1097/md.0000000000021416
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection and intrahepatic cholestasis of pregnancy

Abstract: Background: Viral hepatitis type B is caused by hepatitis B virus (HBV) infection. Several studies have linked HBV infection to a higher risk of developing intrahepatic cholestasis of pregnancy (ICP), although some give contradictory results. To investigate the association and estimated risk of ICP in patients with HBV infection, we conducted this meta-analysis to summarize all available evidence. Methods: This study consists of 2 meta-analyses. A literature search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
(50 reference statements)
0
17
0
1
Order By: Relevance
“…In addition, we also found that the two groups had statistically significant differences in intrahepatic cholestasis during pregnancy ( P < 0.001). In the meta-analysis conducted by Jiang et al [ 25 ], we found that HBV infection was a high-risk factor for intrahepatic cholestasis during pregnancy. Cai et al [ 26 ] also reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we also found that the two groups had statistically significant differences in intrahepatic cholestasis during pregnancy ( P < 0.001). In the meta-analysis conducted by Jiang et al [ 25 ], we found that HBV infection was a high-risk factor for intrahepatic cholestasis during pregnancy. Cai et al [ 26 ] also reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…Zhang et al [61] conducted a large retrospective cohort study (n = 85,190) and showed that pregnant HBV carriers were more likely to present intrahepatic cholestasis of pregnancy (ICP) (OR 3.4, 95% CI 2.80 to 4.13). Additionally, Jiang et al [62] performed a systematic review and meta-analysis on the association between HBV infection and intrahepatic cholestasis (ICP) and demonstrated a higher risk of ICP with OR of 1.68 (95% CI 1.43-1.97; I2 = 0%) among HBV-positive mothers. Moreover, the mothers with ICP also had increased risk of HBV infection.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…In addition, we also found that the two groups had statistically signi cant differences in intrahepatic cholestasis during pregnancy (P < 0.001). In the metaanalysis conducted by Jiang et al [24] , we found that HBV infection was a high-risk factor for intrahepatic cholestasis during pregnancy. Cai et al [25] also reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 88%